2009
DOI: 10.1007/s10709-009-9369-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk for intentional violent death associated with HLA genotypes: a preliminary survey of deceased American organ donors

Abstract: This study investigates the different Human Leukocyte Antigen (HLA) genotypes and their possible associations with both disease and behavior, specifically by describing significant associations between particular HLA genotypes and occurrence of intentional violent death. A de-identified dataset of n = 216,426 deceased American organ donors was analyzed for all possible genotypes by comparing the Independent Variable (Each specific HLA genotype vs. remainder of sample, non-genotype) on the Dependent Variable (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…In accordance with these data, a Tunisian study found the DQB1*02 allele to be the most susceptible and DQB1*05 the most protective in schizophrenia patients [32]. On the other hand, an American study on a huge cohort of mainly Caucasian deceased organ donors [33] which associated intentional violent death with 21 HLA-DR and 10 HLA-DQ alleles found both DQB1*02 and DQB1*05 to be significantly associated with increased risks for violent death.…”
Section: Discussionmentioning
confidence: 71%
“…In accordance with these data, a Tunisian study found the DQB1*02 allele to be the most susceptible and DQB1*05 the most protective in schizophrenia patients [32]. On the other hand, an American study on a huge cohort of mainly Caucasian deceased organ donors [33] which associated intentional violent death with 21 HLA-DR and 10 HLA-DQ alleles found both DQB1*02 and DQB1*05 to be significantly associated with increased risks for violent death.…”
Section: Discussionmentioning
confidence: 71%
“…Over the years, there have been numerous studies on the associations between different HLA alleles and infectious or immune diseases [7][8][9][10][11], but few studies have tried to find associations between HLA genotypes and different behaviors or mental states. For example, associations were found between HLA alleles and suicidal behavior [12,13], between HLA genotypes and aggression [14], and between the HLA system and psychosis [15] or panic disorder [16].…”
Section: Introductionmentioning
confidence: 99%